2022
DOI: 10.3390/healthcare10050791
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Stress, and Social Support in Pregnant Women in the Province of Leon during COVID-19 Disease

Abstract: The COVID-19 pandemic has posed a high risk to the mental health of the entire population. Pregnant women are strongly affected by the consequences of COVID-19, resulting in increased anxiety and stress. Social support can be a protective factor when it comes to mental health disturbances such as anxiety, fear, or stress in pregnant women. This research aims to describe the anxiety and stress of women in the first trimester of pregnancy in times of pandemic and its relationship with social support. A quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Finally, 17 articles were included in the review (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) that measured levels of fear or anxiety in pregnant women during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 17 articles were included in the review (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) that measured levels of fear or anxiety in pregnant women during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing the levels of fear and anxiety in pregnant women was the main objective of this review and both variables were identified in 7 (31)(32)(33)(34)40,42,45) and 13 (30,32,(34)(35)(36)(37)(38)(39)(41)(42)(43)(44)46) studies, respectively. Other factors related to the psychological impact that the COVID-19 pandemic had on the pregnant women were: stress (30,40) or depression (38,39,43,45,46). Both fear and anxiety were assessed using different measurement tools: fear was assessed using, W-DEQ-A (34), FOC-6 (40), and ad hoc Fear scale (42,45).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our results do not show direct correlations with baby weight or NICU admission, other previous studies found a higher risk of having a child with low birth weight [ 83 , 84 ] and other negative pregnancy outcomes like spontaneous abortion [ 85 ], preterm birth or respiratory distress [ 86 ], both associated with NICU admission. The current situation caused by COVID-19 is perceived by pregnant individuals as stressful [ 87 , 88 ] and even though in our study all received information on healthy lifestyle (information on smoking included), the CG maintained their smoking habits. Pregnant individuals who smoked during the pandemic [ 89 ] also had lower frequencies of physical activity [ 90 ] and increased chances of anxiety and depression, as well as showing decreased success in quitting smoking [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, our findings align with studies that reported increased social support during the COVID-19 pandemic perceived by pregnant women. 19,69 On the contrary, it is significant to note that studies reported decreased social support for pregnant women during the COVID-19 pandemic. [70][71][72] Based on such different findings, we noticed that the data about perceived social support in pregnant women during the COVID-19 pandemic is country-specific, similar to the data about maternal anxiety during the COVID-19.…”
Section: Perceived Social Support In Pregnant Women During the First ...mentioning
confidence: 99%